Mechanical and sound absorption performance of addition type liquid silicone rubber reinforced with halloysite nanotubes. (22nd January 2021) - Peng, Longgui; Lei, Lei; Liu, Yongqiang; Du, Lifei
Abstract: Addition-molded room temperature vulcanized liquid silicone rubber (LSR) has become the promising candidate for environmentally friendly sound-absorbing materials, but the absorption efficiency should be further improved. In this study, the Halloysite nanotubes (HNTs) are chosen as the additive with the aim to improve the sound absorption performance of the LSR. Furthermore, the effect of the addition amount of HNTs on the mechanical properties and frequency dependent sound absorption efficiencies are investigated. Results indicate that the fabricated samples show effective high-frequency sound absorption and excellent mechanical properties. The mechanism of the improved sound absorption efficiency in high frequencies is discussed, which is believed to be attributed to the synergistic effect in the multiscale structure: 1) complex interfacial interactions at the surfaces of HNTs; 2) the friction between the air in the cavity and the inner wall of HNTs. Therefore, introducing the HNTs into the traditional silicone rubber would be an efficient way to improve the absorption efficiency for high frequency sound waves.